A Case of Tuberculous Spondylitis in Child with Undernourish - Viorika, Erli Meichory; Yani, Finny Fitry; Sahputra, Roni Eka (Jurnal Kesehatan Andalas, 2021)
Tuberculous spondylitis accounts for around 2% of all cases of Tuberculosis (TB) and around 15% of extrapulmonary TB cases. It has been reported that a 17 years old boy with a complaint of a bump on the lumbar region and felt low back pain since two years before admission with a history of back trauma. There was a decrease of body weight. There was no paraesthesia nor paralysis. Defecation and micturition were normal. Basic immunization was incomplete. On physical examination found palpable lymph nodes 0,5x0,5x0,5 cm, multiple et regio colli. There was no BCG scar. Impression nutritional status was undernourished. There was fixed palpable mass at back size about 5x4x5 cm, hard, no fluctuations, no rebound tenderness. Lung examination was normal. Tuberculin test showed induration sized 20 mm. Gene Xpert result Micobacterium Tuberculosis (MTB) not detected. On chest X-ray examination found L1-2 corpus destruction. MRI Spine was suggestive of compressive fractures and suggestive of a bilateral psoas abscess. Decompression and lumbar stabilization surgery were performed. The histopathology examination results were consistent to spondylitis TB characteristics. The patient was discharged on 6th hospitalization and given anti-tuberculous drug.Keywords: Â bump, extrapulmonary, fracture, spondylitis, tuberculosis